Radiologic practice in the face of COVID-19. The impact on private Radiologic facilities in south-south Nigeria. : Radiologic practice in the face of COVID-19. The impact on private radiologic facilities in south-south Nigeria. - ROBINSON, EBBI (British Journal of Healthcare and Medical Research, 2020)
Abstract Background: CoronaVirus Disease (Covid-19) is a highly contagious disease that has spread to many countries all over the globe and the index case in Nigeria was confirmed on 27th February 2020. The study is aimed at evaluating the impact of the COVID-19 pandemic on private radiologic facilities in south-south Nigeria. Methodology: This was a retrospective survey of 5 private radiologic facilities in Port Harcourt, south-south Nigeria from November 2019 to April 2020 using the facilities monthly statistics. The statistics were evaluated to assess the attendance of patients to radiologic investigation before and during the pandemic. The inclusion criteria are the availability of personal protective equipment (PPE) and radiologic practise guideline in accordance with the COVID-19 pandemic. Records concerning patient’s attendance to Plain radiography, Ultrasonography, Computed tomography, hysterosalpingography, mammography and Magnetic resonance imaging were reviewed. The data collated were analyzed and presented in tables, charts and graphs.Results: The highest number of patients was observed in November 2019 with 2.6% decrease in January, 82.9% and 90.1% decrease in March 2020 and April 2020 respectively. All the centres had a significant reduction in the use of radiologic facilities within this period of the pandemic. The negative economic impact was estimated to be huge drawing an inference from the very poor patient’s turnout. Conclusion: In conclusion, the COVID-19 pandemic was a global catastrophe in radiologic investigation and its impact in private radiologic facilities in Port Harcourt was enormous.